2010
DOI: 10.1002/prca.200900024
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of putative oocyte quality markers by comparative ExacTag proteomics

Abstract: Purpose Identification of the biomarkers of oocyte quality, and developmental and reprogramming potential is of importance to assisted reproductive technology in humans and animals. Experimental design PerkinElmer ExacTag™ Kit was used to label differentially proteins in pig oocyte extracts (oocyte proteome) and pig oocyte-conditioned in vitro maturation media (oocyte secretome) obtained with high- and low-quality oocytes. Results We identified 16 major proteins in the oocyte proteome that were expressed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…The more abundant proteins in high oocyte quality proteome were mainly Kelchlike ECH-associated protein 1 (an adaptor for ubiquitin-ligase CUL3), nuclear export factor CRM1 and Ataxia-telangiectasiamutated protein kinase. In the opposite, Dystrophin (DMD) was more abundant in low-quality oocytes [113].…”
Section: Oocyte In Vitro Maturationmentioning
confidence: 97%
See 2 more Smart Citations
“…The more abundant proteins in high oocyte quality proteome were mainly Kelchlike ECH-associated protein 1 (an adaptor for ubiquitin-ligase CUL3), nuclear export factor CRM1 and Ataxia-telangiectasiamutated protein kinase. In the opposite, Dystrophin (DMD) was more abundant in low-quality oocytes [113].…”
Section: Oocyte In Vitro Maturationmentioning
confidence: 97%
“…Stabilization of the COC matrix and oocyte quality Bovine [101] Oocyte Ubiquitin ligase, nuclear export factors protein, kinase protein Oocyte quality Mouse [113] LAMP1,2, Glyoxylase 1 (GLO1) and ubiquitin Oocyte quality, maturation and competence Bovine and mouse [119,167] TCTP Overexpression increases oocyte maturation Bovine [136] CD55, CD9, CD81, GRP94, BiP (GRP78), ORP150 (hypoxia up-regulated 1), calreticulin, calnexin, PDI Important for fertilization Mouse [119,168,169] HSP70, (HSP1b), HSP90a Important for fertilization Mouse [169][170][171] avb3 integrin, a6b1 integrin Important for fertilization Bovine [169,171] Kelch-like ECH-associated protein 1 (KEAP1) Oocyte quality and maturation Mouse [169,172] Dystrophin (DMD) Over-expression decreases oocyte quality Mouse [113] Bisphosphoglyceratemutase (BPGM) Oocyte maturation and considered as maternal housekeeping protein Mouse [169,172] technology. As a result of assessing murine MII oocytes, beginning with 156-380 unique proteins using 2D electrophoresis coupled to MS [73,74] then 625 proteins with 1D-SDS-PAGE and RP-LC-MS/MS [19] until reaching a profile of 3699 proteins [75], the proteomic obtained information is associated with early development [75].…”
Section: Cumulus Cells (Cont)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that DJ-1 has also been identified as important factor for reprogramming by Miyamoto and colleagues (Miyamoto et al 2011). Furthermore, quality markers, such as kelch-like Ech-associated protein 1 and CRM1, a nuclear export factor, were found to be highly abundant in high-quality porcine oocytes (Powell et al 2010). Another study on porcine oocytes showed that oocytes with the first polar body collected at 42 h of in vitro maturation were more supportive of cloned embryo development than oocytes with the first polar body collected at 33 h (Kong et al 2014).…”
Section: Proteome Analysismentioning
confidence: 96%
“…Such proteins include structural proteins such as actin or tubulin, as well as initiation factors, elongation factor 1, endoplasmic reticulum luminal protein or spermidine aminopropyltransferase. More recently, Powell and colleagues [14], using ExacTag™ labeling kit proteomics, have identified biomarkers of oocyte quality and developmental and reprogramming potential by comparing high and low quality oocytes. The study was conducted at the level of the oocyte itself, as well as the secretome.…”
Section: Proteomics and Reproductionmentioning
confidence: 99%